2014
DOI: 10.1002/bmc.3311
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination and pharmacokinetic study of gambogic acid and gambogenic acid in rat plasma after oral administration of Garcinia hanburyi extracts by LC‐MS/MS

Abstract: Gambogic acid and gambogenic acid are two major bioactive components of Garcinia hanburyi, and play a pivotal role in biologic activity. In this study, a specific and sensitive liquid chromatography-tandem mass spectrometry was developed and validated for simultaneous determination of gambogic acid and gambogenic acid in rat plasma. Chromatographic separation was achieved on a C18 column using an isocratic elution with methanol-10 m m ammonium acetate buffer-acetic acid (90:10:0.1, v/v/v) as the mobile phase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“… 47 GA also exerts moderate efficacy in H22 xenograft tumors with only 45% tumor inhibition after 2 mg/kg ip dosing. 48 …”
Section: Pan-bcl-2 Inhibitors With Anti-mcl-1 Activitymentioning
confidence: 99%
“… 47 GA also exerts moderate efficacy in H22 xenograft tumors with only 45% tumor inhibition after 2 mg/kg ip dosing. 48 …”
Section: Pan-bcl-2 Inhibitors With Anti-mcl-1 Activitymentioning
confidence: 99%
“…Previous studies have confirmed that GNA has a broad spectrum anti-tumor effect in breast cancer cell line, lung cancer cells and other cancer cells (Fan et al, 2013;Zhou et al, 2013;Wang et al, 2014). However, the poor solubility, short biological half-life and excessive vascular irritation of GNA hindered its clinical application (Hua et al, 2015). In order to enhance delivery efficiency and bioavailability of GNA, we have used nanotechnology and successfully prepared PEGylated non-ionic surfactant vesicles and solid lipid nanoparticles of GNA in previous researches (Huang et al, 2013;Lin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al (2007) developed a liquid chromatography-atmospheric pressure chemical ionization-mass spectrometry with single ion monitoring method for the determination of GA in human plasma with LLOQ of 31 ng/mL. Recently, Hua et al (2014) quantified GA and gambogenic acid in rat plasma after oral administration of Garcinia hanburyi extracts by LC-MS. Bioavailability (BA), excretion and tissue distribution for GA were not reported in the above paper. These methods might be sensitive enough for the quantification of GA in biosamples after intravenous injection.…”
Section: Introductionmentioning
confidence: 99%
“…These methods might be sensitive enough for the quantification of GA in biosamples after intravenous injection. Recently, Hua et al (2014) quantified GA and gambogenic acid in rat plasma after oral administration of Garcinia hanburyi extracts by LC-MS. Bioavailability (BA), excretion and tissue distribution for GA were not reported in the above paper.…”
Section: Introductionmentioning
confidence: 99%